PENGARUH QUALITY OF WORK LIFE DAN MODAL PSIKOLOGI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DENGAN KEPUASAN KERJA SEBAGAI MEDIASI (Studi Pada Pegawai Setda Kabupaten Pemalang) - Didah Zakiah Oktaviani, 13520220071; Rijanti, Tristiana (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aims to determine the effect of quality of work life and psychological capital in organizational citizenship behavior and job satisfaction as mediating. This study was to examine and analyze whether job satisfaction plays a role mediating the effect of quality of work life and psychological capital in organizational citizenship behavior.From the test data and analysis, this study provides empirical evidence as follows: (1) Quality of Work Life and psychological capital on job satisfaction. (2) Quality of Work Life has no effect on Organizational Citizenship Behavior. (3) Psychological capital and job satisfaction affect the OCB. (4) Job satisfaction mediates the effect of Quality of Work Life on Organizational Citizenship Behavior. (5) Job satisfaction does not mediate the effect of Psychological Capital on Organizational Citizenship Behavior. Keyword : Quality of Work Life, Psychological Capital, Job Satisfaction, Organizational Citizenship Behavior